Calcium Imaging of Living Astrocytes in the Mouse Spinal Cord following Sensory Stimulation - Giovanni Cirillo; Daniele De Luca; Michele Papa (Neural Plasticity)
Astrocytic Ca2+ dynamics have been extensively studied in ex vivo models; however, the recent development of two-photon microscopy and astrocyte-specific labeling has allowed the study of Ca2+ signaling in living central nervous system. Ca2+ waves in astrocytes have been described in cultured cells and slice preparations, but evidence for astrocytic activation during sensory activity is lacking. There are currently few methods to image living spinal cord: breathing and heart-beating artifacts have impeded the widespread application of this technique. We here imaged the living spinal cord by two-photon microscopy in C57BL6/J mice. Through pressurized injection, we specifically loaded spinal astrocytes using the red fluorescent dye sulforhodamine 101 (SR101) and imaged astrocytic Ca2+ levels with Oregon-Green BAPTA-1 (OGB). Then, we studied astrocytic Ca2+ levels at rest and after right electrical hind paw stimulation. Sensory stimulation significantly increased astrocytic Ca2+ levels within the superficial dorsal horn of the spinal cord compared to rest. In conclusion, in vivo morphofunctional imaging of living astrocytes in spinal cord revealed that astrocytes actively participate to sensory stimulation.